THE EFFECT OF JOB INSECURITY AND WORK FLEXIBILITY ON THE TURNOVER INTENTION OF GENERATION Z EMPLOYEES WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Rahmawati, Intan; Hamdani (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to analyze the influence of job insecurity and work flexibility on turnover intention of Generation Z employees, with job satisfaction as an intervening variable. This research uses a quantitative approach with a survey method involving a sample of 50 Generation Z office employee respondents who work at PT PJM. Data was collected through a questionnaire which was measured using a Likert scale. Data analysis was carried out using the SmartPLS V.40 application to test direct and indirect relationships between variables. The research results show that: 1) Job Insecurity has a negative and significant effect on Job Satisfaction. 2) Work Flexibility has a negative and significant effect on Job Satisfaction. 3) Job Insecurity has a positive and significant effect on Turnover Intention. 4) Work Flexibility has no effect on Turnover Intention. 5) Job Satisfaction has a negative and significant effect on Turnover Intention. 6) Job Satisfaction can mediate the influence of Job Insecurity on Turnover Intention, (7) Job Satisfaction can mediate the influence of Work Flexibility on Turnover Intention.